Enhanced thermoelectric performance of twisted bilayer graphene nanoribbons junction. (April 2019) - Deng, Shuo; Cai, Xiang; Zhang, Yan; Li, Lijie
Abstract: We investigate the electron transport and thermoelectric property of twisted bilayer graphene nanoribbon junction (TBGNRJ) in 0°, 21.8°, 38.2° and 60° rotation angles by first principles calculation with Landauer-Buttiker and Boltzmann theories. It is found that TBGNRJs exhibit a strong reduction of thermal conductance compared with the single graphene nanoribbon (GNR) and negative differential resistance (NDR) in 21.8° and 38.2° rotation angles under ± 0.2 V bias voltage. More importantly, three peak ZT values of 2.0, 2.7 and 6.1 can be achieved in the 21.8° rotation angle at 300 K. The outstanding ZT values of TBGNRJs are interpreted as the combination of the reduced thermal conductivity and enhanced electrical conductivity at optimized angles. Graphical abstract: Image 101